Mesoporous Ga-MCM-41: a very efficient support for the heterogenisation of metallocene catalysts - Campos, João M. (2013)
Mesoporous Ga-containing silicates prepared by direct synthesis, Ga-MCM-41, are used in combination with metallocene Cp2ZrCl2 to provide very effective supported catalysts for ethylene polymerisation. A pre-treatment with methylalumoxane is not required in order to achieve high polymerisation activity levels with these catalysts, whose stability is improved when compared to the case where a purely siliceous support was used for the immobilisation of the metallocene.